2006
DOI: 10.1063/1.2400509
|View full text |Cite
|
Sign up to set email alerts
|

Addressing water vaporization in the vicinity of an exploding wire

Abstract: The phase state of thin (∼1μm) layer of water adjacent to the surface of rapidly heated thin wire 100±50μm in radius is analyzed by computer hydrodynamic calculation. It is shown that when heating of a wire to a temperature of 420°C is achieved in less than ∼500ns, the trajectory of the phase state is contained in the liquid part of the phase diagram. This suggests additional proof of and an explanation for the absence of shunting plasma discharge in fast underwater electrical wire explosions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In earlier research, 19 it was shown that despite a very high temperature of the wire's surface reaching $1 eV, the adjacent water layer may remain in a liquid phase because of high pressure. However, due to a radiation flux emitted by the exploding wire, 16 one obtains ionization of a thin ( 1 lm) layer of water in the vicinity of the exploding wire's surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier research, 19 it was shown that despite a very high temperature of the wire's surface reaching $1 eV, the adjacent water layer may remain in a liquid phase because of high pressure. However, due to a radiation flux emitted by the exploding wire, 16 one obtains ionization of a thin ( 1 lm) layer of water in the vicinity of the exploding wire's surface.…”
Section: Discussionmentioning
confidence: 99%
“…The radius of the Al wire is r 0 ¼ 63:5 lm ¼ 6:35 Â 10 À3 cm. The length of the Al wire is l 0 ¼ 4:5 cm, its initial volume is Q ¼ pl 0 r 2 0 % 5:6 Â 10 À4 cm À3 , the total mass is M % 1:54 mg, and the total number of Al atoms in this wire is N % 3:4 Â 10 19 . The density of Al atoms at normal conditions is qN a =M ¼ 6 Â 10 22 cm À3 ; where N a is the Avogadro number and M is the molar weight of Al.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the shunting channel was explained by the results of computer simulations of the heating process of water and the subsequent generation of acoustic flow by heating a wire submerged in water. According to these calculations the phase trajectory is contained in the liquid part of the phase diagram [23]. Here let us note that 1D MHD calculation, which accounts for radiation transport, showed that for a current amplitude >1 MA the UEWE is accompanied by the formation of a hot (several tens of eV) narrow (∼100 µm radial thickness) plasma channel in the surrounding water.…”
Section: Micro-and Nanosecond Time Scale Uewementioning
confidence: 97%
“…A one-dimension hydrodynamic computer calculation accounting the water equations of state and transport parameters (18) of the heating process of water and the subsequent generation of acoustic flow by heating a wire submerged in water was presented in detailed in Ref. (19). The calculation was performed in order to obtain a trajectory of the phase state of a thin water layer adjacent to the surface of the wire during its heating.…”
Section: Computer Modelling Of the Phase State Of Water Layer Adjacen...mentioning
confidence: 99%